Efficient Risk-Taking and Regulatory Covenant Enforcement in a Deregulated Banking Industry - Joseph P. Hughes; Choon-Geol Moon; Robert DeYoung (Rutgers University, Department of Economics, 2000)
Over the past two decades, a variety of deregulatory measures have increased competition in the U.S. commercial banking industry. While increased competitive rivalry creates incentives for banks to operate more efficiently, it also creates incentives for banks to take additional risk, potentially threatening the safety of banking and payments system. Commercial bank regulators have responded to this increased potential for risk-taking by formally linking bank supervision and regulation to the level of risks that banks take. In this study we analyze the safety and soundness (CAMEL) ratings assigned by bank supervisors to commercial banks, and search for evidence that these ratings reflect not just the level of risk taken by banks, but also the risk-taking efficiency of those banks (i.e., whether taking an increased level of risk generates higher expected returns). We find that supervisors do distinguish between the risk-taking of efficient banks and the risk-taking of inefficient banks, and that they permit efficient banks more latitude in their investment strategies than inefficient banks. However, we also find that supervisors maintain incentives for both efficient and inefficient banks to manage their risk more efficiently.
Keywords: 330